2013
DOI: 10.1021/jm400317w
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Potent Boronic Acid Derived Inhibitor of the HCV RNA-Dependent RNA Polymerase

Abstract: A boronic acid moiety was found to be a critical pharmacophore for enhanced in vitro potency against wild-type hepatitis C replicons and known clinical polymorphic and resistant HCV mutant replicons. The synthesis, optimization, and structure-activity relationships associated with inhibition of HCV replication in a subgenomic replication system for a series of non-nucleoside boron-containing HCV RNA-dependent RNA polymerase (NS5B) inhibitors are described. A summary of the discovery of 3 (GSK5852), a molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 36 publications
(90 reference statements)
0
49
0
Order By: Relevance
“…1). The mechanism of action was confirmed to be inhibition of NS5B by inhibition of its enzymatic activity and cocrystallization with NS5B (30). The antiviral activity of GSK5852 was evaluated on subgenomic replicons derived from the genotype 1a H77, genotype 1b Con1, and genotype 2a JFH-1 strains in replicon assays using the luciferase reporter as a readout as well as the genotype 2a chimeric virus.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1). The mechanism of action was confirmed to be inhibition of NS5B by inhibition of its enzymatic activity and cocrystallization with NS5B (30). The antiviral activity of GSK5852 was evaluated on subgenomic replicons derived from the genotype 1a H77, genotype 1b Con1, and genotype 2a JFH-1 strains in replicon assays using the luciferase reporter as a readout as well as the genotype 2a chimeric virus.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to HCV-796, GSK5852 is still active against C316Y replicons as well as several other mutations that severely impacted HCV-796 activity (Table 3). GSK5852 was found to form a direct hydrogen bond between the boronic acid residue and the tyrosine hydroxyl group in genotype 1b crystal structures, potentially accounting for the retention of activity against C316Y (30). For genotype 1b, most of the single amino acid changes did not result in significant loss of potency except for some changes at position 365.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Voitenleitner et al reported that GSK5852 showed good anti-HCV activity with EC50 values in the nanomolar range against HCV genotypes 1 and 2 and has an excellent resistant profile. This molecule is currently in clinic [147,148]. The Palm II nonnucleoside inhibitors that are currently in different phases of development are given in Table 7.…”
Section: Site IV [Palm Ii]mentioning
confidence: 99%